(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Changes in lifestyle has been one of the leading causes of the increasing numbers of non communicable deseases. According to research done by IGD in 2019, Indonesia faces the double burden of malnutrition with high rates of undernutrition coexisting alongside increasing rates of obesity and Non-communicable Diseases (NCDs). But the good news is that health consciousness is particularly high in Indonesia. Almost all say they’re interested in a healthy diet. In this situation, food industries can play a role in helping Indonesian consumers achieving their overall health status. In terms of availability, food industries can provide more plentiful of nutritious food while trying to be more productive in term of land usage. In terms of affordability, food industries must try to fulfill food and nutrition needs for each individu, while emphasizing food safety as well.